PROBLEMS AND PROSPECTS OF MARINE INSURANCE ON THE NORTHERN SEA ROUTE - G. I. Shepelin (Модернизация, инновация, развитие)
The relevance of the chosen topic due to the increasing significance for Russia, the North Sea Route (NSR). In connection with the sharp increase in the number of Russian and foreign ships passing through the NSR, increasing the need for increased insurance specification of its features in practice. The last is the practice of applying high insurance rates applicable to foreign insurance companies. In the first part of the article assesses the status of NSR and ice explores the risks and practice of insurance, including insurance of construction of the Arctic fleet. The second part discusses the practice of insurance of emergency incidents the Arctic and provides specific recommendations. Finally, the paper suggests some directions of development of insurance on NSR.The purpose / goal. The aim of the article is the analysis of insurance activity in the Arctic, development of proposals for the development of the whole complex of problems in the insurance activities of NSR.Methodology. The methodological basis of the article are economic and statistical methods of analysis of normative-legal documents in the field of insurance, open analyses of the insurance activity in the Arctic.Conclusions / relevance. Practical importance of work consists in the development of proposals for the development and deepening of insurance in the Arctic, which can be applied by legislative and Executive authorities of the Russian Federation in the current activities.